Investigation of the causes of maternal mortality using root cause analysis in Isfahan, Iran in 2013-2014 - Marjan Beigi; Somaye Bahreini; Mahboubeh Valiani; Mojtaba Rahimi; Azar Danesh-Shahraki (Wolters Kluwer Medknow Publications, 2015)
Background: Many maternal deaths caused are due to preventable causes during pregnancy and childbirth. Therefore, the detailed analysis of the root causes provides developing a plan and appropriate interventions to prevent these deaths occurring in the health system. This study aims to determine the causes of maternal mortality using root cause analysis (RCA) method. Materials and Methods: This research is a descriptive explorative study. The data were collected from the files in the maternal health center and the interviews conducted with relevant personnel. The causes of maternal mortality and related reasons were determined by experts' team opinions and through a standard checklist of RCA. Causes consisted of the factors related to health services (human factors and structural factors), maternal family and social status, and maternal disease status. For each of these factors, analysis was performed to determine the root. In the end, interventional suggestions were developed to prevent the recurrence of similar deaths. Results: Causes were classified into human factors, and structural factors in the area of planning and management and social status of mothers. The results showed that human factors were composed of lack of knowledge and skills in the medical team, unfamiliarity with their duties, lack of health care-based on protocols, etc. Structural factors included lack of follow-up after discharge and inadequate supervision of inspectors on academic qualified doctors. Maternal social and family status factor included lack of referral the mothers' to the health care center. Conclusions: Based on the RCA process, the most fundamental factor in creating these deaths was management errors at the level of universities and the Ministry of Health. These errors included inadequate supervision of medical education, failure to identify and introduce the instructions and guidelines related to the care of pregnant mothers by the health workers and experts, and lack of collective strategies to inform the public about the type and model of self-care in health centers. Based on the obtained results, the solutions proposed for elimination of root causes of maternal death are organizing sequential training courses tailored for the staff taking care of pregnant women, sending guidelines related to maternal health care to all private and public institutions, and informing the community to receive health care services by health centers and mass media.